2021
DOI: 10.1080/01431161.2020.1864059
|View full text |Cite
|
Sign up to set email alerts
|

Replacing human interpretation of agricultural land in Afghanistan with a deep convolutional neural network

Abstract: Afghanistans annual opium survey relies upon time-consuming human interpretation of satellite images to map the area of potential poppy cultivation for statistical sample design. Deep Convolutional Neural Networks (CNNs) have shown groundbreaking performance for image classification tasks by encoding local contextual information, in some cases outperforming trained analysts. In this study, we investigate the development of a CNN to automate the classification of agriculture from medium resolution satellite ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…DL has gained many successes in prediction/classification quests. Among all the DL structures, convolutional neural network (CNN) [ 18 , 19 ] is particularly suitable for analyzing 2D/3D images. To help boost the performance of CNN, researches are proposed to modify CNN structures in terms of either depth, or cardinality, or width.…”
Section: Methodsmentioning
confidence: 99%
“…DL has gained many successes in prediction/classification quests. Among all the DL structures, convolutional neural network (CNN) [ 18 , 19 ] is particularly suitable for analyzing 2D/3D images. To help boost the performance of CNN, researches are proposed to modify CNN structures in terms of either depth, or cardinality, or width.…”
Section: Methodsmentioning
confidence: 99%
“…Recent work has shown the potential to produce accurate and timely agricultural land classification from satellite imagery using convolutional neural networks (CNNs) [6,7]. These deep learning models differ from conventional pixel-and object-based approaches in that they can be trained across multiple years of image data using transfer learning: where a pre-trained model is fine tuned using new labelled image data from a much smaller dataset than was used to train the original model.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [6] found that transfer learning in Afghanistan's Helmand Province between years required 75% less labelled data than models trained from scratch (no prior training), with improved overall accuracy (>94%).…”
Section: Introductionmentioning
confidence: 99%
“…The moving window integrates time-varying delay information hidden in time series data into the input layer of the CNN. As a result of powerful feature extraction capability, CNN is not only used in image processing [ 16 ], but also in manufacturing industry [ 17 ], which is used to extract the data characteristics of variables in the cement calcination process.…”
Section: Introductionmentioning
confidence: 99%